Water stress responses of seedlings of four Mediterranean oak species (Tree Physiology, 2000)
Effects of water stress on phenology, growth, stomatal activity and water status were assessed from April to November 1996 in 2-year-old seedlings of Quercus frainetto Ten. (Quercus conferta Kit.), Quercus pubescens Willd., Quercus macrolepis Kotschy (Quercus aegilops auct.) and Quercus ilex L. growing in containers in northern Greece. All four species developed more than 50% of their total leaf area before the beginning of June—an adaptation to arid climates. Well-irrigated plants tended to develop greater individual leaf area, number of leaves per plant, total plant leaf area, height and root:shoot ratios than water-stressed plants, but the difference between treatments was not significant for any parameter in any species. Quercus macrolepis appeared to be the most drought-tolerant of the four species. It maintained the highest number of leaves of the smallest size and increased the proportion of fine roots during drought. In all species, drought caused significant decreases in stomatal conductance and predawn and midday water potentials from mid-July until the end of August, when the lowest soil water content and highest mean daily air temperatures and midday leaf temperatures occurred; however, the responses were species-specific. Among the four species, Quercus macrolepis sustained the highest stomatal conductance despite very low water potentials, thus overcoming drought by means of desiccation tolerance. Quercus ilex decreased stomatal conductance even before severe water stress occurred, thereby avoiding dessication during drought. Quercus pubescens had the highest water potential despite a high stomatal conductance, indicating that its leaf water status was independent of stomatal activity. Quercus frainetto was the least drought-resistant of the four species. During drought it developed very low water potentials despite markedly reduced stomatal aperture.
10.1093/treephys/20.16.1065